EXERCISE THERAPY PROGRAM IN SECONDARY SPONTANEOUS PNEUMOTHORAX ASSOCIATED WITH PULMONARY TUBERCULOSIS: A CASE REPORT - Irayanti, Winda; Wijianto, W; Utami, Mulatsih Nita; Hidayati, Ratna Nur Rahma (Academic Physiotherapy Conference Proceeding, 2021)
Introduction: Secondary spontaneous pneumothorax (PSS) occurs due to underlying lung disease, in some developing countries pulmonary tuberculosis (TB) is the primary cause of PSS. Case Presentation: A 37 years-old male patient who was farmer from Wonogiri, Central Java, came to RS Paru Dungus with the symptoms of dyspnea, cough, and chest pain for 3 months ago. The patient is an active smoker for 25 years and quits smoking 3 months ago. The patient has a history of pulmonary TB disease. On examination of vital signs, blood pressure and heart rate were good, the patient's breathing was 28x/minute, oxygen saturation was 90%. A chest X-ray showed suggestive pleural TB with secondary infection and pneumothorax in the left apical segment. Based on the inspection, the patient using diaphragmatic breathing, has a barrel chest, and kyphosis. On palpation, there was a spasm of the accessory muscles of respiration. Auscultation showed normal breath sounds and hyper resonance in the left superior area. Vocal fremitus in left superior lobe > left inferior lobe. The dyspnea scale was 6 while the functional activity examination showed the patient was on a scale of 4. Management and Outcome: Physiotherapists give breathing control (BC), deep breathing exercise (DBE), and chest expansion resistance exercise (CERE) training programs for 9 days, getting the results of decreasing dyspnea level and increasing the patient's functional activity. Discussion: Pneumothorax secondary to TB usually occurs after extensive TB involvement of the lung as sudden bronchopleural fistulization and empyema with severe cavitary formations cause pleural rupture. BC is given to patients with a respiratory rate >20x/min, to help improve inefficient or abnormal breathing patterns, while DBE can increase ventilation and oxygenation, and CERE is given to maximize lung expansion by increasing the amount of air that can be pumped by the lungs to maintain the performance of the respiratory accessory muscles. Conclusion: Exercise therapy can reduce shortness of breath and improve functional activity in patients with secondary spontaneous pneumothorax associated pulmonary TB.